1.            26 = 3*3+11+6

2.            20 = 3*3+10+1

3.         17 = 3*0+10+7

4.             16 = 3*2+7+3

5.  .       14 = 3*1+7+4

6.            14 = 3*1+6+5

7.            13 = 3*1+5+5

8.         13 = 3*1+6+4

9.            13 = 3*0+8+5

10.             13 = 3*0+6+7

11. .      11 = 3*1+5+3

12.   8 = 3*0+5+3

 

 

1.            3

2.            3

3.             2

4.  .       1

5.            1

6.            1

7.         1

8.  .      1

9.         0

10.           0

11.             0

12.   0

 

 

1.            11

2.            10

3.         10

4.            8

5.             7

6.  .       7

7.            6

8.         6

9.              6

10.           5

11. .      5

12.   5

 

 

1.         7

2.              7

3.            6

4.            5

5.            5

6.            5

7.  .       4

8.         4

9.             3

10. .      3

11.   3

12.           1

 

 

( )

1.            26 = 3*3+11+6

2.         20 = 3*3+10+1

3.            17 = 3*0+10+7

4.              16 = 3*2+7+3

5.            14 = 3*1+6+5

6.            14 = 3*1+7+4

7.  .       13 = 3*1+5+5

8.  .      13 = 3*1+6+4

9.             13 = 3*0+6+7

10.   13 = 3*0+8+5

11.        11 = 3*1+5+3

12.           8 = 3*0+5+3

 

- 2022-2023

 

1-

 

                                        ..             ..        

1.             1  1  0  0  3 - 1    3  (26= 3*3+11+6)        (14= 3*1+6+5)       +

2.             1  1  0  0  3 - 0    3  (20= 3*3+10+1)        (17= 3*0+10+7)      +

 

3.              1  1  0  0  2 - 0    3  (16= 3*2+7+3)         (13= 3*0+6+7)       +

4.  .        1  0  1  0  1 - 1    1  (14= 3*1+7+4)         (13= 3*1+5+5)       =

5.             1  0  1  0  1 - 1    1  (13= 3*1+5+5)         (14= 3*1+7+4)       =

6.          1  0  1  0  1 - 1    1  (13= 3*1+6+4)         (11= 3*1+5+3)       =

7.             1  0  1  0  0 - 0    1  (13= 3*0+8+5)         (8= 3*0+5+3)        =

8.  .       1  0  1  0  1 - 1    1  (11= 3*1+5+3)         (13= 3*1+6+4)       =

9.     1  0  1  0  0 - 0    1  (8= 3*0+5+3)          (13= 3*0+8+5)       =

10.         1  0  0  1  0 - 3    0  (17= 3*0+10+7)        (20= 3*3+10+1)      -

 

11.            1  0  0  1  1 - 3    0  (14= 3*1+6+5)         (26= 3*3+11+6)      -

12.              1  0  0  1  0 - 2    0  (13= 3*0+6+7)         (16= 3*2+7+3)       -

 

1-

 

- . 1:1   {1+5+5}-{1+7+4}

- (0+0+2); - (0+0+1); - (0+0+1); -- (0+1+0); - (1+1+0); - (0+1+0); - (0+0+0); - (0+1+0); - (0+1+0); - (0+0+1);

- (0+0+2); - (0+0+0); - (0+0+1); - (0+2+1); - (0+1+0); - (0+1+0); - (1+1+0); - (0+1+0); - (0+0+0); - - (0+1+0);

 

- 3:0   {3+10+1}-{0+10+7}

- (0+0+0); - (0+1+1); - (0+1+0); - (0+1+0); - (2+2+0); - (0+1+0); - (0+1+0); - (0+0+0); - (1+2+0); - (0+1+0);

- (0+0+2); - (0+0+1); - (0+2+0); - (0+1+0); - (0+1+0); - (0+2+1); - (0+2+1); - (0+1+2); - (0+1+0);

 

- 2:0   {2+7+3}-{0+6+7}

- (0+1+1); - (0+0+1); - (1+2+0); - (0+1+0); - (0+1+0); - (1+1+0); - (0+1+0); - (0+0+0); - (0+0+1); - (0+0+0);

- (0+0+4); - (0+1+1); - (0+0+1); - (0+0+0); - (0+1+0); - (0+1+0); - (0+2+1); - (0+1+0);

 

- 0:0   {0+8+5}-{0+5+3}

- (0+0+2); - (0+1+1); - (0+0+1); - (0+0+0); - (0+1+0); - (0+1+0); - (0+2+1); - (0+1+0); - (0+1+0); - (0+1+0); - (0+0+0);

- (0+0+0); - (0+0+1); - (0+0+1); - (0+1+0); - (0+1+0); - (0+1+0); - (0+1+0); - (0+0+0); - (0+1+0); - (0+0+1);

 

- 1:3   {1+6+5}-{3+11+6}

- (0+0+0); - (0+1+2); - (0+0+1); - (0+0+1); - (0+1+0); - (1+2+1); - (0+1+0); - (0+1+0); - (0+0+0); - (0+0+0); - (0+0+0);

- (0+0+0); - (0+0+1); - (0+0+1); - (0+2+0); - (1+1+0); - (1+2+1); - (1+1+0); - (0+2+1); - (0+0+1); - (0+2+1); - (0+1+0);

 

. - 1:1   {1+5+3}-{1+6+4}

- (0+0+2); - (0+0+1); - (0+1+0); - (0+2+0); - (0+0+0); - (1+1+0); - (0+1+0); - (0+0+0);

- (1+1+1); - (0+1+2); - (0+0+1); - (0+1+0); - (0+1+0); - (0+1+0); - (0+1+0); -Gamid Agalarov (0+0+0); - (0+0+0); - (0+0+0);

 

 

 

1.      ( )   8 = 3*2+2+0

2.      ()             6 = 3*1+2+1

3.          ()             6 = 3*1+2+1

4.      ()          5 = 3*1+1+1

5.            ( )    5 = 3*1+2+0

6.     ()             5 = 3*1+2+0

7.       . ()        4 = 3*1+1+0

8.        ()        4 = 3*1+1+0

9.          ()          4 = 3*1+1+0

10.               ()            4 = 3*1+1+0

11.        ()         4 = 3*1+1+0

12.       . ()        4 = 3*1+1+0

13.       ()               4 = 3*0+0+4

14.    ()             3 = 3*0+2+1

15. . ()          3 = 3*0+2+1

16.          ()          3 = 3*0+1+2

17.         ()          3 = 3*0+2+1

18.          ()          3 = 3*0+2+1

19.      ()          3 = 3*0+1+2

20.    ()             3 = 3*0+2+1

21.         ()             3 = 3*0+2+1

22.         ()             3 = 3*0+1+2

23.     ()               3 = 3*0+2+1

24.     ()            2 = 3*0+0+2

25.         ()             2 = 3*0+1+1

26.          . ()        2 = 3*0+0+2

27.       ()     2 = 3*0+0+2

28.     ()          2 = 3*0+2+0

29.       ()             2 = 3*0+2+0

30.    ()          2 = 3*0+0+2

31.       ()              2 = 3*0+1+1

32.      . ()       2 = 3*0+0+2

33.         . ()         2 = 3*0+2+0

34.     ()               2 = 3*0+1+1

35.       ()             2 = 3*0+1+1

36.        ()        1 = 3*0+0+1

37.         ()            1 = 3*0+1+0

38.       ()        1 = 3*0+1+0

39.      ()            1 = 3*0+1+0

40.       ()        1 = 3*0+1+0

41.       ()        1 = 3*0+1+0

42.     . ()        1 = 3*0+0+1

43.         . ()       1 = 3*0+1+0

44.     . ()         1 = 3*0+1+0

45.      . ()         1 = 3*0+1+0

46. -   . ()     1 = 3*0+1+0

47.       ()       1 = 3*0+0+1

48.        ()       1 = 3*0+1+0

49.      ()       1 = 3*0+1+0

50.      ()     1 = 3*0+1+0

51.    ()       1 = 3*0+1+0

52.     ()    1 = 3*0+0+1

53.       ()    1 = 3*0+0+1

54.         ()    1 = 3*0+1+0

55.    ()  1 = 3*0+1+0

56.        ()   1 = 3*0+1+0

57.       ()1 = 3*0+1+0

58.        ()   1 = 3*0+1+0

59.    ()   1 = 3*0+0+1

60.             ()         1 = 3*0+0+1

61.       ()     1 = 3*0+1+0

62.    ()     1 = 3*0+1+0

63.        ()        1 = 3*0+1+0

64.            ()        1 = 3*0+0+1

65.         ()        1 = 3*0+0+1

66.          ()          1 = 3*0+0+1

67.         ()          1 = 3*0+1+0

68.      ()           1 = 3*0+0+1

69.      ()            1 = 3*0+0+1

70. - ()    1 = 3*0+1+0

71.       ()            1 = 3*0+1+0

72.     ()            1 = 3*0+1+0

73.         ()        1 = 3*0+1+0

74.         ()            1 = 3*0+0+1

75.   ()         1 = 3*0+0+1

76. ()             1 = 3*0+1+0

77.       ()             1 = 3*0+1+0

78.   ()         1 = 3*0+1+0

79.      ()             1 = 3*0+0+1

80.        ()            1 = 3*0+0+1

81.         ( )          1 = 3*0+0+1

82.         ()           1 = 3*0+1+0

83.          ()           1 = 3*0+1+0

84.         ()           1 = 3*0+1+0

85.        . ()      1 = 3*0+0+1

86.         . ( )      1 = 3*0+1+0

87.               . ()        1 = 3*0+1+0

88.       ()             1 = 3*0+0+1

89.      ()              1 = 3*0+1+0

90.         ()          1 = 3*0+1+0

91.      ()          1 = 3*0+1+0

92.        ()           1 = 3*0+1+0

93.         ()           1 = 3*0+1+0

94.      ()            1 = 3*0+1+0

95.            ()            1 = 3*0+1+0

96.           ( )   1 = 3*0+1+0

97.         ()        0 = 3*0+0+0

98.       ()        0 = 3*0+0+0

99.         ()          0 = 3*0+0+0

100.        ()             0 = 3*0+0+0

 

1.      ( )   8 = 3*2+2+0

2.      ()             6 = 3*1+2+1

3.          ()             6 = 3*1+2+1

4.      ()          5 = 3*1+1+1

5.            ( )    5 = 3*1+2+0

6.     ()             5 = 3*1+2+0

7.      ()     5 = 3*1+2+0

8.            ( )         5 = 3*1+2+0

9.       . ()        4 = 3*1+1+0

10.       ()        4 = 3*1+1+0

11.         ()          4 = 3*1+1+0

12.               ()            4 = 3*1+1+0

13.        ()         4 = 3*1+1+0

14.       . ()        4 = 3*1+1+0

15.       ()            4 = 3*1+1+0

16.         ()                  4 = 3*1+1+0

17.       ()               4 = 3*0+0+4

18.      ( )          3 = 3*1+0+0

19.        . ()     3 = 3*1+0+0

20.   ()        3 = 3*1+0+0

21.          ()                  3 = 3*1+0+0

22.           ()               3 = 3*1+0+0

23.    ()             3 = 3*0+2+1

24. . ()          3 = 3*0+2+1

25.          ()          3 = 3*0+1+2

26.         ()          3 = 3*0+2+1

27.          ()          3 = 3*0+2+1

28.      ()          3 = 3*0+1+2

29.    ()             3 = 3*0+2+1

30.         ()             3 = 3*0+2+1

31.         ()             3 = 3*0+1+2

32.     ()               3 = 3*0+2+1

33.       ()              3 = 3*0+2+1

34.     ()            2 = 3*0+0+2

35.         ()             2 = 3*0+1+1

36.          . ()        2 = 3*0+0+2

37.       ()     2 = 3*0+0+2

38.     ()          2 = 3*0+2+0

39.       ()             2 = 3*0+2+0

40.    ()          2 = 3*0+0+2

41.       ()              2 = 3*0+1+1

42.      . ()       2 = 3*0+0+2

43.         . ()         2 = 3*0+2+0

44.     ()               2 = 3*0+1+1

45.       ()             2 = 3*0+1+1

46.        ()             2 = 3*0+2+0

47.         ()            2 = 3*0+0+2

48.         ()             2 = 3*0+1+1

49.            . ()          2 = 3*0+2+0

50.      ( )2 = 3*0+2+0

51.         ()     2 = 3*0+0+2

52. ( )2 = 3*0+2+0

53.    ( )       2 = 3*0+0+2

54.     ( )   2 = 3*0+2+0

55.       ()            2 = 3*0+0+2

56.        ( )   2 = 3*0+2+0

57.        ()             2 = 3*0+1+1

58.     ( )   2 = 3*0+2+0

59.     ( )         2 = 3*0+2+0

60.        ( )         2 = 3*0+2+0

61.        ()        1 = 3*0+0+1

62.         ()            1 = 3*0+1+0

63.       ()        1 = 3*0+1+0

64.      ()            1 = 3*0+1+0

65.       ()        1 = 3*0+1+0

66.       ()        1 = 3*0+1+0

67.     . ()        1 = 3*0+0+1

68.         . ()       1 = 3*0+1+0

69.     . ()         1 = 3*0+1+0

70.      . ()         1 = 3*0+1+0

71. -   . ()     1 = 3*0+1+0

72.       ()       1 = 3*0+0+1

73.        ()       1 = 3*0+1+0

74.      ()       1 = 3*0+1+0

75.      ()     1 = 3*0+1+0

76.    ()       1 = 3*0+1+0

77.     ()    1 = 3*0+0+1

78.       ()    1 = 3*0+0+1

79.         ()    1 = 3*0+1+0

80.    ()  1 = 3*0+1+0

81.        ()   1 = 3*0+1+0

82.       ()1 = 3*0+1+0

83.        ()   1 = 3*0+1+0

84.    ()   1 = 3*0+0+1

85.             ()         1 = 3*0+0+1

86.       ()     1 = 3*0+1+0

87.    ()     1 = 3*0+1+0

88.        ()        1 = 3*0+1+0

89.            ()        1 = 3*0+0+1

90.         ()        1 = 3*0+0+1

91.          ()          1 = 3*0+0+1

92.         ()          1 = 3*0+1+0

93.      ()           1 = 3*0+0+1

94.      ()            1 = 3*0+0+1

95. - ()    1 = 3*0+1+0

96.       ()            1 = 3*0+1+0

97.     ()            1 = 3*0+1+0

98.         ()        1 = 3*0+1+0

99.         ()            1 = 3*0+0+1

100.   ()         1 = 3*0+0+1